Differential reinforcement to decrease stereotypy exhibited by an adult with autism spectrum disorder. (3rd December 2020) - Butler, Courtney; Kobylarz, Ashley; Zaki‐Scarpa, Christeen; LaRue, Robert H.; Manente, Christopher; Kahng, SungWoo
Abstract: Motor and vocal stereotypies are behaviors commonly exhibited by individuals with autism spectrum disorder (ASD). Stereotypy may impede and interfere with learning new skills and decrease work performance in employment settings. Previous research has evaluated effective interventions for stereotypy; however, they have typically focused on treating stereotypy exhibited by children in structured settings. We evaluated the practicality of implementing a simple differential reinforcement of other behavior procedure with an adult with ASD in multiple, naturalistic environments. Results showed rapid decreases in motor and vocal stereotypies upon implementation of the intervention and maintenance of low levels of behavior. These data highlighted the successful treatment of stereotypy exhibited by an adult with a long history of exhibiting these behaviors. Treatment effects were replicated across multiple, naturalistic environments.